Courses perceived difficult by undergraduate students majoring in biology - Ahmad Fauzi; Anisa Fariantika (Universitas Negeri Jakarta, 2018)
Some previous reports inform many students having learning difficulties on some science subjects. The purpose of this study is to map the courses considered difficult by undergraduate students majoring in Biology. This study used survey research design. Participants in this study are undergraduate students of Biology Education Study Program and undergraduate students of Biology Study Program, from the Department of Biology in one of the state university in Malang. The instruments used in this study are questionnaires of difficult courses in the Department of Biology and descriptive analysis is used as a data analysis technique. The results of this study are the majority of Biology Education students positioning Genetics, Genetics, and Biochemistry as the first, second, and third most difficult courses, while the majority of Biology students positioning Genetics, Genetics, and Botany as the first, second, and third most difficult courses. The Genetics, Statistics, and Biochemistry are the three most frequently selected courses as the three most difficult subjects in Biology Education Study Program, while in Biology Study Program is Genetics, Biochemistry, and Botany.